2022
DOI: 10.3390/su14031585
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Willingness to Allow Their Unaccompanied Children to Use Emerging and Future Travel Modes

Abstract: This study investigated parents’ willingness to allow their unaccompanied child(ren) to use emerging and future travel modes (e.g., rideshare vehicles and automated vehicles). An online survey was completed by 631 Australian respondents (M = 39.2 years, SD = 10.5 years, Male: 36.6%) who reported that they currently lived with one or more children (17 or below). Approximately one-third (37.9%) of the respondents reported a willingness to allow their child to use a rideshare vehicle alone and more than half of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 39 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…On the other hand, trust also might be a barrier to modal choice as reported by Garrard [ 46 ] that trust in others (for both personal and traffic safety) plays a main barrier to children’s active travel to school and independent mobility. Trust also might be a barrier for children to travel in current or future car-sharing modes [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, trust also might be a barrier to modal choice as reported by Garrard [ 46 ] that trust in others (for both personal and traffic safety) plays a main barrier to children’s active travel to school and independent mobility. Trust also might be a barrier for children to travel in current or future car-sharing modes [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most prior studies, it has been concluded that fathers are more likely to allow their children to use autonomous mobility as a school travel mode [7,31,32,35]; however, no significant relation was found by Ayala et al [33] or Anania [36]. Parents' education level is another demographic factor that positively influenced their intentions to use AVs in most studies [9,31,32,34]; however, Mao et al [7] found no significant relationship between these two factors. Different and contradictory findings have also been reported for the effect of income on parents' intention.…”
Section: Literature Reviewmentioning
confidence: 97%
“…The effect of familiarity with automation technology is another demographic factor that has been examined by prior studies. In most of the studies, a significant and positive relation has been found [7,9,31]. The number of children and owning a driving license were other explanatory variables that were considered by Mao et al [7], but no significant associations were found between these variables and parents' intentions to use automation.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…'Q}N= |xyO QO u; Q}otWJ CiQW}B w u= QOwN |Qw=: vi Qwy_ xm OwQ|t Q=_Dv= 40 smCUO Vy=m 'l}i= QD QO |QwxQy@ V}=Ri= %xrtH R= 'C@Ft |=yOt=}B =@ QO xm |O= Qi= |= Q@ |QwDwt |O= Qiv= |DmQL |=ypLx= Q |x= Q= w |Dwi |=yhO=YD QO |OH CQwY x@ 'OvDU}v |oOvv=Q x@ QO=k =} OvQ=Ov |oOvv=Q |xR=H= Q[=L p=L C}r@=k |= Q=O u= QOwN |Qw=: vi [84] "OQ=Po@ Q}F -=D O= Qi= QiU Q=DiQ w pkvwptL Q= R=@ O= Qi= w u=mOwm 'u=Ovtr=U QDtm |}=v=wD =@ O= Qi= |= Q@ XwYN x@ |oOvR \}=QW Ow@y@ |= Q@ ?U=vt |xv}Ro l} u=wva x@ 'q=@ |=yp}Uv=DB p}rO x@ w xOw@ C}OwOLt |= Q=O C=ar=]t xJQo [10 w 9] "CU= xOW |iQat u= Rwt;Vv=O |r}YLD QiU C}i}m Ow@y@ |oOvR hrDNt |=yx@vH QO u= QOwN |wQOwN R= xO=iDU= ptDLt |=}= Rt Q@ |Q=}U@ xO=iDU= uOW Q}o xty CQwY QO \ki =}=Rt u}= , =a]k =t= [1511 w 8 '5] 'Ov=xOQm O}m -=D l} |iQat R= V}B 'K}LY |=y|Q=PoCU=}U pwYLt xm 'O=O Ovy=wN |wQ u; R= [16] "CU= Q= R=@ x@ pwYLt u= Rwt;Vv=O %CU= Cw=iDt uq=UoQR@ =@ hrDNt p}qO x@ u=mOwm pkvwptL Q=DiQ uwO@ OvQ=Ov xR=H= ?re= w OvQ=O OYkt ?=NDv= OQwt QO |QDtm |=y?=NDv= , qwtat |=yCi=Ut Ovv=wD|tv =yv; "Ovvm QiU O=tDa= OQwt uq=UoQR@ =} u}Or=w |y=Qty x}rkv p}=Uw |]}Lt |=yO}OyD Q@=Q@ QO w Ovvm|t CmQL QDxDUy; 'OvwQ@ x= Q |vqw] xUQOt x@ Ot; w CiQ QO OwN u}Or=w x@ ?re= w OvDUy QDQ}PB? }U; u=ov=o}@ =} xOQm sqa= 1 WHO |v=yH CW=Oy@ u=tR=U |Q=t; |=yVQ= Ro [1] "Ov=xDU@=w xr=U 14 =D 5 u=mOwm Q}t w nQt |rY= pra R= |m} '|}xO=H |=yhO=YD xm CU= =y=]N xm CU= xOW xO=O u=Wv |Q=}U@ C=ar=]t QO u}vJty [2] "CU= u=yH QO EO=wL R= OYQO 93 |r= 90 QO ptDLt =} |a]k Cra l} ' |v=Uv= |=yOw@tm w [3] "CU= xOW |UQQ@ pwUt xOvU}wv "1402 1 28 VQ}PB '1402 1 26 |= Q@ = Q OwN x= Qty uwO@ OvRQi x@ uO=O xR=H= x@ u=oOvyOMU=B p}=tD x@ \w@Qt |O}rm xR=H= x@ u=oOvyOMU=B p}=tD "CU= xO=O u=Wv [21] "=}r= QDU= w [19] u}J [22 w 9] '=m}Qt; QO xrtH R= 'CU= xOW s=Hv= xar=]t = Q u}Or=w |ivt =} C@Ft ?=NDv= QO QFwt pt=wa 'u}W}B C=ar=]t ?re= P=ND= x@ QO=k xm |v}Or=w OYQO 'QwmPt C=ar=]t ?re= QO xm |r=L QO &Ov=xOQm h=Oy= R= |m} xm =Hu; R= "CU= |UQQ@ p@=k 'Ov=xOw@v XwYN u}= QO s}tYD CW=O Q_v QO O}=@ 'CU= |Qw=: vi VQ}PB `v=wt `iQ w |UQQ@ 'C=ar=]t xvwou}= = Q sQ=Ov |Q_v |xv}Ro xm |O= Qi= |= Q@ '`v=wt `iQ w |Qw=: vi VQ}PB p=tDL= xm "CU= QDW}@ 'Ov=xOQm ?=NDv= = Q Q}N |xv}Ro xm |O= Qi= x@ C@Uv 'Ov=xOQm ?=NDv= ?=NDv= pOt l} '=OD@= 'u}W}B C=ar=]t QDW}@ hqNQ@ 'Q[=L |xar=]t QO u}vJty QDW}@ xm |r=L QO &CU= xOW xQ@}r=m hrDNt pt=wa u=tRsy QF= |UQQ@ |= Q@ xDUUo "Ov=xOQm OwOLt |i}YwD Q=t; p}rLD w x} RHD x@ = Q OwN |=yp}rLD 'u}W}B C=ar=]t xt=vVUQB l} 'x@=Wt C=ar=]t |UQQ@ R= TB w Q[=L VywSB s=Hv= Qw_vt x@ p}mWD w =yMU=B Ci=} QO 'hrDNt [17] "CU= xOW xDiQ}PB 3 NHTSA |rt |=yx= Q |m}i=QD |vt}= "Ovm|t Q}}eD u= QOwN , qt=m |oOvv=Q 5 K]U =D |DUO , qt=m |oOvv=Q QiY K]U R= [18] "CU= wQOwN C=v=mt= w |oOvv=Q QO u=Uv= Cr=NO u= R}t QO QwmPt Kw]U Cw=iD xDN=vW pt=m |v=QOwN u=wva x@ xm 'u= QOwN |wQOwN…”
mentioning
confidence: 99%